Characterization of the complete mitochondrial genome of Meira sp. (Exobasidiales: Brachybasidiaceae) with phylogenetic analysis - Yuanhang Ren; Lidan Lu; Maoling Tan; Yanan Cao; Lianxin Peng (Mitochondrial DNA. Part B. Resources, 2020)
In this study, the complete mitochondrial genome of Meira sp. was sequenced and assembled. The complete mitochondrial genome of Meira sp. has 15 protein-coding (PCG) genes, 2 ribosomal RNA (rRNA) genes, and 22 transfer RNA (tRNA) genes. The mitochondrial genome of Meira sp. has a total size of 23,353 bp, with the base composition as follows: A (30.62%), T (32.82%), G (17.84%) and C (18.73%). Phylogenetic analysis indicated that the mitogenome of Meira sp. exhibited a close relationship with the mitogenome of Jaminaea angkorensis.